Pengaruh Elemen Visual terhadap Respon dan Keterlibatan Emosional dalam Desain Poster Kampanye Sosial - I Gusti Agung Rangga Lawe (Pusat Riset dan Inovasi Nasional, 2025)
Social campaign posters are one of the visual communication media that has an important role in conveying public messages, shaping perceptions, and encouraging changes in social behavior in society. With visual power, posters can express messages directly, effectively, and emotionally to the audience. This study aims to examine how key visual elements—color, typography, imagery, and layout—affect the emotional response and audience engagement to social campaign messages. A qualitative approach was used by collecting data through visual observation of a number of selected social campaign posters, design analysis, and literature review from relevant literature. The results of the analysis show that each visual element has a significant contribution to the power of the message. Colors, for example, are able to evoke emotional resonance by influencing the mood of the audience, such as the color red that conveys urgency or the color green that represents expectations and the environment. Imagery or illustrations provide the power of imagination and help the audience connect the message with social reality. Proper typography improves readability, emphasizes the main message, and establishes the desired tone of communication. Meanwhile, a well-planned layout creates a visual flow that makes it easier for the audience to understand the message in order. The harmonious interplay between colors, typography, imagery, and layout has been proven to strengthen visual appeal, evoke empathy, and motivate audiences to participate in social campaigns.